Social interaction and the development of cognitive operations - Doise, Willem; Mugny, Gabriel; Perret-Clermont, Anne-Nelly (My University, 1975)
This paper presents two experiments to support the general hypothesis that the coordination of actions between individuals promotes the acquisition of cognitive coordinations. The first experiment shows that two children, working together, can successfully perform a task involving spatial coordinations; children of the same age, working alone, are not capable of performing the task. The second experiment shows that subjects who did not possess certain cognitive operations involved in Piaget's conservation of liquids task acquire these operations after having actualized them in a social coordination task.